2012
DOI: 10.1590/s1516-35982012001200006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea polyphenols, insulin-like growth factor I and glucose on developmental competence of bovine oocytes

Abstract: -The present study examined the effects of green tea polyphenols (GTP), insulin-like growth factor-I (IGF-I) and glucose on oocyte in vitro maturation, subsequent embryo development and blastocyst quality in bovine. Cumulus-oocyte complexes (COC) were aspirated from the ovaries and cultured in synthetic oviduct fluid supplemented with MEM amino acids (SOFaa) media supplemented with one of the following supplements: GTP (0, 10, 15 and 20 μM), IGF-I (0, 50, 100 and 150 ng/mL) or glucose (0, 1.5, 5.6 and 20 mM) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Substantial improvements in preserved (liquid or freezing storage) semen quality traits and sperm fertilization [ 130 , 131 , 133 , 134 ], oocyte development and competence, and embryo development [ 15 , 16 , 139 , 140 ] have been reported. The other evidence that could be observed from in vitro studies is that supplementation of polyphenolic compounds during gametes or embryo in vitro manipulation might continue to in vivo animals.…”
Section: Polyphenols and In Vitro Assisted Reproduction Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial improvements in preserved (liquid or freezing storage) semen quality traits and sperm fertilization [ 130 , 131 , 133 , 134 ], oocyte development and competence, and embryo development [ 15 , 16 , 139 , 140 ] have been reported. The other evidence that could be observed from in vitro studies is that supplementation of polyphenolic compounds during gametes or embryo in vitro manipulation might continue to in vivo animals.…”
Section: Polyphenols and In Vitro Assisted Reproduction Techniquesmentioning
confidence: 99%
“…These facts explain the negative effects observed in some studies due to addition of high levels of polyphenols. For instance, bovine oocytes cultured in maturation medium supplemented with 15 μM/mL green tea polyphenols (99% catechin) derivatives, mainly EGCG, have higher intracellular glutathione (GSH) concentrations, maturation and cleavage rates, and blastocyst rates than those supplemented with 20 μM/mL [ 15 ]. In agreement with these observations, it has been stated that supplementation of a lower EGCG concentration (10 μg/mL) during in vitro fertilization significantly increased fertilization rate, while higher EGCG concentration (25 μg/mL) decreased fertilization rate [ 64 ].…”
Section: Polyphenols and In Vitro Assisted Reproduction Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…(97) IGF-1. Wang et al (98) reported that supplementation with polyphenols at 15 μM, 100 ng/mL IGF-1, and 5.6 mM glucose produced higher cleavage and blastocyst rates than did polyphenols at other concentrations. The authors concluded that these compounds could improve oocyte maturation, embryo development, and blastocyst quality in cattle.…”
Section: Evidence On the Effect Of Growth Factorsmentioning
confidence: 99%